The perception of psychological stress in the nursing profession at Daro Hospital, Sarawak: a case study - Mahdi, Abdul Khalid; Adam Assim, Mohamad Ibrani Shahrimin; Hasbie, Siti Nur Rohani (Human Resources Management Academic Research Society (HRMARS), 2024)
Nursing is a professional field in health care. Nurses assume responsibility for the healing and maintenance of safety for those who are terminally ill, for the maintenance of health for those who are healthy, and for managing anxiety in all life-threatening situations in all areas of healthcare. Nurses need to be given psychosocial support so that their mental well-being is maintained because they are workers who protect the interests of society. This case study involved two nurse supervisors as informants who were serving in health facilities and the input was study data in the form of audio-verbal interviews which had been transcribed into case study material. Participating observation is also documented as secondary data. Significant literature highlights and the results of freelance studies are used as secondary sources before the training process is carried out. The objective of this study is to examine qualitative cases of perceptions about the level of psychological stress in the nursing profession at Daro Hospital, Sarawak. The studies are carried out in the form of qualitative investigations, namely case studies, to absorb data from open-ended questions. It can provide in-depth information about the causes of psychology and is appropriate to get a true picture of the themes and sub-themes that have been set. Its use also allows the development of the concepts and understanding necessary to make judgments and provide suggestions regarding the issues under study. In relation to the results of the study, several important factors formed from the main themes of the study will be submitted to the Ministry of Health Malaysia in an effort to explore the qualitative process of psychological stress in the nursing profession.